Regional aspect of investment security of Ukraine (Economics and region, 2019)
The state of investment security of Ukraine at the regional level is investigated on the basis of calculation of coefficients of heterogeneity of spatial distribution of capital investments and direct foreign investments. The uneven distribution of capital investments by region of Ukraine allows us to analyze the degree of spatial heterogeneity and its dynamics to assess its impact on the overall investment security of the state in terms of ensuring its stable high level. The authors describe that reducing the level of investment security at the regional level will raise the need for regional policy aimed at developing state programs of regional socio-economic development. They enable the disclosure of investment potential in the relevant territory by direct investors through their participation, in particular, in national investment projects.
Keywords: investments; direct foreign investments; economic growth; investment security